Tradisi Sinoman Sebagai Sistem Pertukaran Sosial Di Dalam Pelaksanaan Pesta Pernikahan Adat Jawa (Studi Pada Masyarakat Transmigrasi Di Desa Pasir Jaya Kecamatan Rambah Hilir Kabupaten Rokan Hulu) - Ambarwati, Linda Tri Retno; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study is about â€œsinoman tradition as social exchange system in cultural javanish wedding partyâ€. This study explains sinoman traditional values as a social exchange system in wedding party, and the exchange tradition between the society. This study was conducted in desa Pasir Jaya Kecamatan Rambah Hilir Kabupaten Rokan Hulu, Riau.This is a descriptive qualitative research. This research explains the data thourgh logical thinking to get logical summary about data analyzed, so we can get the vivid picture of the situation sistematically about the factors related to the phenomena without using statistical quantification. Data collecting rechnique is snowball with observation, interview, and documentation.Based on data analysis, the summary of sinoman tradition about social exchange system is there is mutualism and long term exchange between society member. The call this as saving for future, because they will get this too when they hold wedding party later on.In sinoman tradition, the terms exchange are not only money but also food supply for wedding consumption.Key Word: Sinoman, Exchange System, Social Status